PERBEDAAN ORIENTASI KARIR ANTARA PRIA DAN WANITA : PENGARUHNYA PADA JENJANG KARIR YANG DICAPAI OLEH WANITA - Hapsari, Ira Maya (PERMANA, 2010)
Is that true, that carrier ladder whose woman achieved was influenced by her orientation in work? When have a carrier, women state that satisfaction is number one, not a higher position in the organizational hierarchy. This article also investigated, do the carrier ladder between man and woman along the similar path? Woman, actually have a bigger barrier than man do to achieving their carrier. Those big barrier coming from the gender discrimination that have no end, which always we can find it easy in every form of organization, in every country, eventhough in the country which claim themselves put the emancipation on the top of them declaration of nation. Despite that, woman must be have a double role, in office she is a working woman, but in home, she must be a good housewife. Those little explaination, why the path of carrier ladder who along man an woman different in many ways.Keywords: carrier, gender discrimination, carrier orientation, carrier ladder